Correction of B0 eddy current effects in spiral MRI. Issue 4 (16th November 2018) - Robison, Ryan K.; Li, Zhiqiang; Wang, Dinghui; Ooi, Melvyn B.; Pipe, James G.
Abstract : Purpose : B0 eddy currents are a subtle but important source of artifacts in spiral MRI. This study illustrates the importance of addressing these artifacts and presents a system response‐based eddy current correction strategy using B0 eddy current phase measurements on a phantom. Methods : B0 and linear eddy current system response measurements were estimated from phantom‐based measurement and used to predict residual eddy current effects in spiral acquisitions. The measurements were evaluated across multiple systems and gradient sets. The corresponding eddy current corrections were studied in both axial spiral‐in/out TSE and sagittal spiral‐out MPRAGE volunteer data. Results : Correction of B0 eddy currents using the proposed method mitigated blurriness in the axial spiral‐in/out images and artifacts in the sagittal spiral‐out images. The system response measurement was found to yield repeatable results over time with some variation in the B0 eddy current responses measured between different systems. Conclusions : The proposed eddy current correction framework was effective in mitigating the effects of residual B0 and linear eddy currents. Any spiral acquisition should take residual eddy currents into account. This is particularly important in spiral‐in/out acquisitions.